2014
DOI: 10.1016/j.stemcr.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Lineage Conversion of Adult Mouse Liver Cells and B Lymphocytes to Neural Stem Cells

Abstract: SummaryOverexpression of transcription factors has been used to directly reprogram somatic cells into a range of other differentiated cell types, including multipotent neural stem cells (NSCs), that can be used to generate neurons and glia. However, the ability to maintain the NSC state independent of the inducing factors and the identity of the somatic donor cells remain two important unresolved issues in transdifferentiation. Here we used transduction of doxycycline-inducible transcription factors to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 31 publications
(40 reference statements)
1
41
0
Order By: Relevance
“…Hes3 expression in vivo has been implicated as an indicator of the efficacy of a g-secretase inhibitor (that blocks Notch signaling) in models of breast cancer (81). Recent studies have implicated Hes3 (still largely in a correlative manner) in different reprogramming paradigms (mouse embryonic fibroblasts to induced pluripotent cells and direct adult to induced NSCs) by demonstrating Hes3 expression regulation during reprogramming and by correlating Hes3 transduction of adult cells with successful reprogramming to induced NSCs (82,83).…”
Section: Notch Signaling In Neural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hes3 expression in vivo has been implicated as an indicator of the efficacy of a g-secretase inhibitor (that blocks Notch signaling) in models of breast cancer (81). Recent studies have implicated Hes3 (still largely in a correlative manner) in different reprogramming paradigms (mouse embryonic fibroblasts to induced pluripotent cells and direct adult to induced NSCs) by demonstrating Hes3 expression regulation during reprogramming and by correlating Hes3 transduction of adult cells with successful reprogramming to induced NSCs (82,83).…”
Section: Notch Signaling In Neural Developmentmentioning
confidence: 99%
“…However, Hes1 expression is much broader than the pattern of ectopic pancreas formation in the Hes1-null mice, suggesting that additional mechanisms could contribute to Ptf1a control or the control of other genes helping to limit ectopic pancreas generation. Hes3 and Hes5, genes with established roles in neural development and specification (5,74,82,83,95,96), are also expressed in the developing stomach and small intestine, respectively (24,97), so they could be candidates as cocontrollers of pancreas organogenesis. Another interesting member of the Hes/Hey gene family is Hes6, a proneural gene implicated in glioma progression (98) …”
Section: Early Clues For the Involvement Of Alternative Hes/hey Genesmentioning
confidence: 99%
“…This may be in part due to the post-mitotic state of the target cell type (neuronlike cells), with the conversion procedure including a halt in proliferation, thus limiting the ability of these cells to expand once reprogrammed [98][99][100] . In addition to determining methods of increasing conversion efficiency, studies have expanded into investigating whether similar methods could be utilised for generation of proliferative neural stem and progenitor cells, which are both expandable in vitro and capable of generating multiple neural cell types [101] , with initial studies demonstrating the generation of induced neural progenitor [101] and crest [102] cells.…”
Section: Generation Of Induced Neural Stem and Progenitor Cellsmentioning
confidence: 99%
“…Furthermore, a number of studies also demonstrated the generation of induced neuroblasts [106] , and induced oligodendrocyte [107,108] and dopaminergic neuron [109] progenitor cells. While the majority of studies utilised fibroblasts as the starting cell type, there have also been reports of the direct conversion of astrocytes [106,110] , Sertoli cells [111] , epitheliallike cells in urine [112] , cord blood-derived stem cells [113] , bone marrow-derived stem cells [114] , liver cells, and B lymphocytes [99] into induced neural stem and progenitor cells, as summarised in Table 3. Generation of induced neural stem and progenitor cells has been achieved using a variety of approaches.…”
Section: Generation Of Induced Neural Stem and Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation